Guidelines for community-driven water resource management: as initiated by the Integrated Water Resource Management Demonstration Projects in Malawi, Mozambique, Namibia, Swaziland and Zambia - van Koppen, Barbara (SADC/Danida Water Sector Support Programme, 2009)
These guidelines are based on the IWRM Demonstration Projects in Malawi, Mozambique, Namibia, Swaziland and Zambia, implemented by the SADC Regional Water Sector Programme supported by Danida, and synthesized by Barbara van Koppen. It provides a practical step-by-step guide on how to apply community-driven water resource management for improved livelihoods and sustainable water systems for multiple uses. The guideline is aimed at implementers of community water development projects, in particular the local government.